(untitled) (University Journal of Zoology, Rajshahi University, 2008)
A study was carried out on the optimal dose of inorganic fertilizer used in carp polyculture system over a period of 10 months. Three treatments were assigned: without inorganic fertilizer, with the application of 100 kg/ha/month inorganic fertilizer and 150 kg/ha/month inorganic fertilizer as T1, T2 and T3, respectively. Each treatment had three replications. The selected indigenous carp species were Rui (Labeo rohita), Catla (Catla catla) and Mrigal (Cirrhinus mrigala), and exotic carp species were silver carp (Hypophthalamichthys molitrix), grass carp (Ctenopharyngodon idella), common carp (Cyprinus carpio) and thai sarpunti (Barbodes gonionotus). The average water area of the experimental ponds was 0.11±0.01 ha and average depth of water in all ponds was 1.26 m. The treatments showed no effect on water temperature, dissolved oxygen, alkalinity and pH. The fish production was significantly higher (P>0.05) in both the treatments T2 and T3 than that of T1 where no inorganic fertilizer was used. But there was no significant difference between T2 and T3 and T2 was with lower dose inorganic fertilizer (100 kg/ha/month) than T3. Therefore, 100 kg/ha/month inorganic fertilizers may be suggested in carp polyculture system for better production. Key words: Inorganic fertilizer, optimal dose, Polyculture, Fish production. Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 77-80